2020
DOI: 10.5194/acp-20-6055-2020
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous oxidation of amorphous organic aerosol surrogates by O<sub>3</sub>, NO<sub>3</sub>, and OH at typical tropospheric temperatures

Abstract: Abstract. Typical tropospheric temperatures render possible phase states of amorphous organic aerosol (OA) particles of solid, semisolid, and liquid. This will affect the multiphase oxidation kinetics involving the organic condensed-phase and gaseous oxidants and radicals. To quantify this effect, we determined the reactive uptake coefficients (γ) of O3, NO3, and OH by substrate films composed of single and binary OA surrogate species under dry conditions for temperatures from 213 to 313 K. A temperature-contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 167 publications
(265 reference statements)
2
60
0
Order By: Relevance
“…Laboratory studies have shown that an organic-rich outer shell is always formed for hydrophobic organic compounds in a LLPS scenario, possibly shielding the interior from surface reactions with gas-phase oxidants (McNeill et al, 2007;Li et al, 2020). The organic-rich outer shell (Arangio et al, 2015;Houle et al, 2018) could be viscous, and the het-erogeneous reactivity could be limited by the diffusion of organic species or oxidants across the organic outer shell.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies have shown that an organic-rich outer shell is always formed for hydrophobic organic compounds in a LLPS scenario, possibly shielding the interior from surface reactions with gas-phase oxidants (McNeill et al, 2007;Li et al, 2020). The organic-rich outer shell (Arangio et al, 2015;Houle et al, 2018) could be viscous, and the het-erogeneous reactivity could be limited by the diffusion of organic species or oxidants across the organic outer shell.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
“…Organic compounds present at or near the surface of atmospheric aerosols can be efficiently reacted with gas-phase oxidants, such as OH, ozone (O 3 ) and nitrate radicals (George and Abbatt, 2010;Kroll et al, 2015;Chapleski et al, 2016), continuously changing aerosol properties (e.g., water uptake and cloud formation potential) through the alteration of surface and bulk composition (Lambe et al, 2007;Cappa et al, 2011;Harmon et al, 2013;Slade et al, 2015Slade et al, , 2017. The physical state of aerosol particles (and their separate phases, when present) is known to play a role in the heterogeneous reactivity of organic aerosols (Ruehl et al, 2013;Chan et al, 2014;Slade and Knopf, 2014;Li et al, 2020). However, the heterogeneous reactivity of aqueous droplets containing organic compounds and inorganic salts remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Any interaction between gas-phase species and condensed matter, including liquid, semi-solid, and solid phases, commences by adsorption and desorption processes (McNaught and Wilkinson, 2014;Langmuir, 1918Langmuir, , 1916Langmuir, , 1915. Those are of importance in the research areas of catalysis and, in particular, multiphase chemical kinetics or phase transfer kinetics involving environmental surfaces and interfaces (Cussler, 2009;Chorkendorff and Niemantsverdriet, 2007;Finlayson-Pitts and Pitts, 2000;Ravishankara, 1997;Solomon, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Especially at low temperatures, large values of τd could counteract slow rates of chemical reaction and diffusion, enhancing the overall gas uptake which may involve reversible, reactive, and catalytic processes on the surface or in the bulk of the particles (Ammann et al, 2013;Crowley et al, 2013;Kolb et al, 2010;Pöschl et al, 2007;Li et al, 2020;Li and Knopf, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Line 61: The authors might add the recent study by Li et al (2020) on OH uptake by organic matter in various phase states.…”
mentioning
confidence: 99%